Integration of waqf and islamic microfinance for poverty reduction: case of Pakistan - Shirazi, Nasim Shah; Obaidullah, Mohammed; Haneef, Mohamed Aslam (Islamic Economics and Finance Research Division, 2015)
Pakistan has been facing a high incidence of poverty. Despite its persistent efforts to make a dent on poverty, the country never witnessed a systematic reduction in the same. The country has been spending a significant amount on safety nets and social protection programs. Some programs provide direct cash grants and other forms of indirect support to the poor, while microfinance programs provide microcredit, micro savings and micro insurance to the beneficiaries. The government extends full support to the microfinance industry and seeks to provide an enabling environment for its successful operation. As a result, the microfinance industry in Pakistan has been flourishing and steadily enhancing its outreach. However, despite all the efforts, it currently covers just about 10 percent of the market in 2013. In Pakistan, initiatives for Islamic microfinance have been undertaken by a few NGOs and financial institutions. Almost all IMIs function below operational self- sufficiency (OSS) and financial-selfsufficiency (FSS) levels. Most of IMIs are unable to increase their outreach due to the human and financial constraints. They face a constrained supply of funds as well as human resources. This paper posits that the constraints are more apparent than real. Islamic finance must include as part of the formal financial system, its time-tested institution of waqf involving endowment of both financial and real assets for community empowerment. The IMIs should be well aware of how to create and put to use such community assets for the economic and social betterment of the community. The paper sought the opinion of beneficiaries on waqf- Islamic microfinance integrated model and discussed the same with the professionals and practitioners. The beneficiaries were not aware of the main components of the waqf-microfinance integrated model, but professionals and practitioners, invariably supported the integrated model while voicing some concerns that should be considered while formulating policies for the sector